2009
DOI: 10.2319/072507-345.1
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of Metallic Brackets After Dental Bleaching

Abstract: Objective: To test the hypothesis that there is no difference between the action of at-home and in-office vital bleaching on the shear bond strength of metallic brackets bonded with composite resin 24 hours after bleaching. Materials and Methods: Forty-five human upper premolars were randomly divided into three groups: (1) control, (2) 10% carbamide peroxide at-home bleached, and (3) 35% hydrogen peroxide in-office bleached. Twenty-four hours after bleaching the teeth were pumiced, bonded with metallic bracket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 15 publications
8
21
0
4
Order By: Relevance
“…6,18 In this regard, the control group and group V showed higher SBS; the amount of residual adhesive was also larger than in the other groups. In agreement with the findings of a previous study, 30 less residual adhesive has been found after dental bleaching with peroxides. This may be explained by the idea that the effects of the chemical agents cause a bond failure on the enamel bonding interface.…”
Section: Adhesive Remnant Indexsupporting
confidence: 93%
See 2 more Smart Citations
“…6,18 In this regard, the control group and group V showed higher SBS; the amount of residual adhesive was also larger than in the other groups. In agreement with the findings of a previous study, 30 less residual adhesive has been found after dental bleaching with peroxides. This may be explained by the idea that the effects of the chemical agents cause a bond failure on the enamel bonding interface.…”
Section: Adhesive Remnant Indexsupporting
confidence: 93%
“…The use of 30%, 20 35%, 19,24,30 and 38% 29 hydrogen peroxide bleaching systems 24 hours before bonding significantly reduced the SBS orthodontic brackets; nevertheless, if the procedure is performed 7 days before bonding, it does not significantly reduce the force required to debond the brackets. 28 Under the conditions of the present study, the use of 38% hydrogen peroxide did not significantly affect the SBS; however, the mean value of that group was 2.4 MPa lower than that of the control group.…”
Section: Discussion Sheer Bond Strengthmentioning
confidence: 96%
See 1 more Smart Citation
“…Although there is no consensus, 11 there is evidence of significant decreases in the mean bond strength of orthodontic brackets when bonding is performed immediately after bleaching, 6,8,12 and strong recommendations have been made to wait several days before undertaking any adhesive procedure. [13][14][15] Accordingly, the purpose of this study was to determine the effects of different etching times with a bleaching treatment of 35% hydrogen peroxide on the shear bond strength of polycrystalline ceramic brackets bonded with different resins for different etching times. The null hypothesis asserted that there is no significant difference in bond strength when using different resins and enamel treatments.…”
Section: Introductionmentioning
confidence: 99%
“…de los brackets se realizó entre 7 y 14 días después del aclaramiento dental, pero sí identifi caron que existió mucha variación en los datos en los primeros 7 días, por lo que sugieren posponer por lo menos 1 semana el proceso de adhesión cuando el aclaramiento dental sea necesario (21). Chandrashekar et al, encontraron valores de RFC mayores en el grupo control y los menores en el grupo donde los brackets fueron cementados inmediatamente después del proceso de aclaramiento dental (22), estos datos son similares a los encontrados en nuestro estudio y a los reportados por otros investigadores (23,24). Vahid et al, compararon distintas concentraciones y tipos de agentes aclaradores, incluido el peróxido de hidrógeno al 40% encontrando que todos los agentes redujeron la capacidad adhesiva al ser sometidos a la prueba de RFC pero no demostraron diferencias signifi cativas entre los grupos a excepción del grupo control donde los valores fueron más altos (25).…”
Section: Discussionunclassified